1989
DOI: 10.1007/bf00297454
|View full text |Cite
|
Sign up to set email alerts
|

Altered islet amyloid polypeptide (amylin) gene expression in rat models of diabetes

Abstract: Summary. The response of the islet amyloid polypeptide gene to chronic dexamethasone treatment in adult rats was investigated. After 12 daily injections, rats were severely underweight and fasting blood glucose levels were elevated. When pancreatic mRNA was analysed, a 16-fold elevation in islet amyloid polypeptide mRNA was observed with only a fourfold increase in insulin mRNA levels. Pancreatic islet amyloid polypeptide and insulin mRNA levels were also determined 12 days after streptozotocin treatment. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(33 citation statements)
references
References 6 publications
2
31
0
Order By: Relevance
“…In streptozotocin-diabetic rats, IAPP and insulin mRNA expressions are reduced to 24 and 15 % of that in controls at day 7 [66], as examined by in situ hybridisation, thereby confirming the initial observations [55]. The phenomenon is neither species-specific nor agent-specific because a similar regulation was observed in alloxan-treated mice [66].…”
Section: Overexpression Of Iapp In Experimental Diabetessupporting
confidence: 76%
See 2 more Smart Citations
“…In streptozotocin-diabetic rats, IAPP and insulin mRNA expressions are reduced to 24 and 15 % of that in controls at day 7 [66], as examined by in situ hybridisation, thereby confirming the initial observations [55]. The phenomenon is neither species-specific nor agent-specific because a similar regulation was observed in alloxan-treated mice [66].…”
Section: Overexpression Of Iapp In Experimental Diabetessupporting
confidence: 76%
“…2). In situ hybridisation to IAPP and insulin mRNA confirmed that IAPP expression is more highly up-regulated than that of insulin after dexamethasone treatment for 12 days [55,62]. Whereas IAPP mRNA expression is increased at the cellular level, insulin mRNA expression is actually down regulated by dexamethasone treatment.…”
Section: Overexpression Of Iapp In Experimental Diabetesmentioning
confidence: 78%
See 1 more Smart Citation
“…This mechanism could certainly compound the effects of IAPP oligomers once hyperglycemia supervenes. Since hyperglycemia and insulin resistance increase the expression rate of IAPP to a greater extent than insulin (53,54), hyperglycemia might also further enhance apoptosis due to IAPP oligomers.…”
Section: Discussionmentioning
confidence: 99%
“…With this enhanced hormonal release, impaired intracellular IAPP processing may initiate the process of amylin aggregation. For instance, dexamethasone treatment for up to 12 days led to increased levels of both proinsulin and Iapp mRNA in rat islets (Bretherton-Watt et al 1989, Koranyi et al 1992. Similarly, both enhanced plasma amylin levels and amylin secretion from isolated pancreata were found in dexamethasone-induced IR rats (Pieber et al 1993, Mulder et al 1995.…”
Section: Effects Of Gcs On Somatostatin Amylin and Ghrelin Releasementioning
confidence: 92%